Persistence of pain and suffering in cancer patients: challenges of pain management from the perspective of nurses - Mangolian Shahrbabaki, Parvin; Farokhzadian, Jamileh; Ahmadi, Fazlollah; Khabbazzadeh, Fatemeh (Frontiers in Pain Research, 2024)
PurposeCancer patients often experience pain, which can greatly reduce their quality of life. It affects their emotions, cognitive function, and daily interactions. Healthcare providers need to understand the obstacles to pain management to create helpful programs for patients and families. This study focuses on Iranian nurses' views on pain management barriers in cancer patients.MethodsThe study utilized a qualitative content analysis method with a purposive sampling approach, involving 27 nurses. Participants were selected to ensure a wide range of perspectives and experiences by considering factors such as gender, age, work experience, education levels, and positions until data saturation was achieved. Inclusion criteria specified a minimum of six months of oncology ward experience and a bachelor's degree or higher in nursing. Nurses with less than six months of oncology experience or lacking a nursing degree were excluded. Data collection was conducted through semi-structured interviews and analyzed using Lundman and Granheim's qualitative content analysis method.ResultsOne main theme, four main categories, and nine subcategories in the study reflected the nurses' experiences and viewpoints about barriers to pain management. These categories included the marginalization of complementary medicine, medical malpractice, inadequate organizational infrastructure, and personal barriers.ConclusionThe study demonstrated that the barriers to pain management in cancer patients were complex. To improve patients' comfort and quality of life, it is important to identify and address issues from different angles. It is crucial to train patients and healthcare providers in pain management and to address weaknesses in the healthcare system.